Centella asiatica Mitigates NMDA Receptor Antagonist-Induced Locomotor Enhancement in Zebrafish (Danio rerio) - Cahayani, Wike Astrid; Masykur, Umar Jundullah; Putri, Dwi Sandhi Aulia Pramesti; Giri, Nyoman Deva Pramana; Sakinata, Naura Syifa; Rohmah, Afifatur (Smart Medical Journal, 2024)
Introduction: In exploring the complexities of the central nervous system and its disorders, animal models have proven indispensable for replicating human neurological conditions and investigating potential therapeutic interventions. Zebrafish, with their genetic and neurobiological similarities to mammals, have become a valuable model for studying neuroactive substances. This study aimed to assess the effects of Centella asiatica on MK-801 induced hyperactivity in zebrafish, bridging the gap between traditional herbal medicine and neuropharmacology. Methods: An experimental design was employed, utilizing adult zebrafish acclimatized under standard laboratory conditions, divided into three groups: a control group without any treatment, a group exposed to 5 µM of MK-801, and a group treated with 5 µM of MK-801 followed by Centella asiatica extract at a concentration of 10 µg/L. Swimming velocity served as the primary measure of locomotor activity, analyzed using Ethovision XT software.Results: The study found that MK-801 significantly increased swimming velocity in zebrafish, indicative of induced hyperactivity. Conversely, subsequent treatment with Centella asiatica notably reduced this hyperactivity, aligning swimming velocities closer to those observed in the control group.Conclusion: Centella asiatica demonstrated significant potential to mitigate MK-801 induced hyperactivity in zebrafish, underscoring its neuroprotective properties. This research highlights the therapeutic promise of natural compounds in neuropharmacology and the utility of zebrafish as a model organism in neuroscience research. Further investigation into Centella asiatica's mechanisms of action and its application in other models of neurological disorders is warranted.